2015
DOI: 10.1080/14786419.2015.1040792
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Melittis melissophyllum L. subsp. melissophyllum iridoidic fraction

Abstract: The analysis of the polar fraction of Melittis melissophyllum L. subsp. melissophyllum led to the identification of several iridoid glycosides: monomelittoside (1), melittoside (2), harpagide (3), acetyl-harpagide (4) and ajugoside (5). Compounds 3 and 4 are considered marker compounds for the genus and, as well as compounds 1, 2 and 5, were already evidenced in a previous study on the nominal species. It was noteworthy of the presence of allobetonicoside (6) which was never reported for this genus. The isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The isoscutellarein derivatives ( 3 and 4 ), containing two sugars in their structure, are also important because of allose as the saccharidic residue. These compounds present acetyl groups on allose, have been evidenced in several genera of the Lamiaceae family, thus confirming their own chemotaxonomic relevance. They were proved to be potent antioxidant compounds and to exert neuroprotective effect on Alzheimer disease …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The isoscutellarein derivatives ( 3 and 4 ), containing two sugars in their structure, are also important because of allose as the saccharidic residue. These compounds present acetyl groups on allose, have been evidenced in several genera of the Lamiaceae family, thus confirming their own chemotaxonomic relevance. They were proved to be potent antioxidant compounds and to exert neuroprotective effect on Alzheimer disease …”
Section: Resultssupporting
confidence: 59%
“…Harpagide ( 6 ) and its derivative 8‐ O ‐acetyl‐harpagide ( 7 ) are chemotaxonomic markers for several genera included in the Lamiaceae family. Monomelittoside ( 8 ) was identified in this species for the first time whereas it was already known in other members of the Stachys genus and in the family itself …”
Section: Resultsmentioning
confidence: 84%
“…Ajuga tenorei and Ajuga chamaepitys ) [25,26], although its presence was also signaled in a few Lamioideae species as Melittis melissophyllum subsp. melissophyllum [19] and species of the genera Stachys and Sideritis . The occurrence of 1 in the Stachys genus is limited to a few species such as B. officinalis (syn.…”
Section: Discussionmentioning
confidence: 99%
“…The eluting system was a mixture of n -BuOH/H 2 O (82:18 v/v). From this chromatographic separation (Scheme 1) 11 compounds were isolated and identified by comparison with data reported in literature and/or by comparison with pure compounds available in our laboratory: Verbascoside (10, 12.4 mg) [14] from the assembly of fractions 8-15; stachysoside A (11, 11.2 mg) [8,15] in mixture with verbascoside (1:2) in the assembly of fractions 17-24; b-arbutin (9, 3.2 mg) [16] from the assembly of fractions 30-32; reptoside (6) [17] and 6-O-acetyl-ajugol (7) [18] in mixture in ratio 1:1.5 (25.0 mg) from the assembly of fractions 43-45; ajugoside (1, 113.7 mg) [17,19] as pure compound from the assembly of fractions 53-54; 8-O-acetyl-harpagide (2, 1.0 g) [20] from the assembly of fractions 70-88; chlorogenic acid (8) [21] in mixture with 8-O-acetyl-harpagide (2) in ratio 1:2 (109.4 mg) from the assembly of fractions 95-112; harpagide (3) [22] and chlorogenic acid (8) in mixture 3:1 (48.3 mg) from the assembly of fractions 118-122; allobetonicoside (4) and chlorogenic acid (8) in mixture 10:1 (29.1 mg) from the assembly of fractions 133-135; allobetonicoside (4, 100.7 mg) [23] as a pure compound from the assembly of fractions 144-163; 4¢-O-galactopyranosyl-teuhircoside (5) [6] in mixture with allobetonicoside (4) in ratio 3:1 (24.7 mg) from the assembly of fractions 166-169.…”
Section: Methodsmentioning
confidence: 99%
“…Only a couple of previous works have focused on the composition of the essential oil from this particular subspecies [3,8], while no study has ever been made of the polar fraction. With the idea of completing the molecular pattern of this species and continuing our recent study on this genus [9], which showed the presence of monomelittoside, melittoside, harpagide, 8-O-acetyl-harpagide, ajugoside and allobetonicoside, we have then decided to proceed with the analysis of a sample of subsp. albida collected in Central Italy.…”
mentioning
confidence: 99%